Effects of Reentry Plasma Sheath on Mutual-Coupling Property of Array Antenna - B. W. Bai; X. P. Li; Y. M. Liu; J. Xu (International Journal of Antennas and Propagation)
A plasma sheath enveloping a reentry vehicle would cause the failure of on-board antennas, which is an important effect that contributes to the “blackout” problem. The method of replacing the on-board single antenna with the array antennas and using beamforming technology has been proposed to mitigate “blackout” problem by many other researchers. Because the plasma sheath is a reflective medium, plasma will alter the mutual coupling between array elements and degrade the beamforming performance of array antenna. In this paper, the effects of the plasma sheath on the mutual coupling properties between adjacent array elements are studied utilizing the algorithm of finite integration technique. Results show that mutual coupling coefficients of array elements are deteriorating more seriously with the decrease of collision frequency. Moreover, when electron density and collision frequency are both large, plasma sheath improves the mutual coupling property of array elements; this conclusion suggests that replacing the on-board single antenna with the array antennas and using beamforming technology can be adopted to mitigate the blackout problem in this condition.